1996
DOI: 10.1007/bf00196642
|View full text |Cite
|
Sign up to set email alerts
|

Cytokinin controls the cell cycle at mitosis by stimulating the tyrosine dephosphorylation and activation of p34cdc2-like H1 histone kinase

Abstract: In excised pith parenchyma from Nicotiana tabacum L. cv. Wisconsin Havana 38, auxin (naphthalene-1-acetic acid) together with cytokinin (6-benzylaminopurine) induced a greater than 40-fold increase in a p34cdc2-like protein, recoverable in the p13suc1-binding fraction, that had high H1 histone kinase activity, but enzyme induced without cytokinin was inactive. In suspension-cultured N. plumbaginifolia Viv., cytokinin (kinetin) was stringently required only in late G2 phase of the cell division cycle (cdc) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
164
2
5

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(183 citation statements)
references
References 34 publications
(55 reference statements)
12
164
2
5
Order By: Relevance
“…Cytokinins were first discovered for their role in promoting cell division (1) and have since been implicated in stimulating both the G 1 3S phase transition (32) as well as the G 2 3M phase transition of the cell cycle (33). The reduced meristem activity seen in the triple mutant roots seems to be a consequence of a delay in the G 2 3M phase, as demonstrated by FACS experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Cytokinins were first discovered for their role in promoting cell division (1) and have since been implicated in stimulating both the G 1 3S phase transition (32) as well as the G 2 3M phase transition of the cell cycle (33). The reduced meristem activity seen in the triple mutant roots seems to be a consequence of a delay in the G 2 3M phase, as demonstrated by FACS experiments.…”
Section: Discussionmentioning
confidence: 99%
“…The Tyr phosphatase activity of the enzyme specific for the CDK is positively regulated by cytokinins (Zhang et al, 1996). In human cells, cdc25 is also involved in the response to UV-mediated DNA damage in a p53-independent pathway, where DNA damage induces S-phase arrest via activation of Chk1 kinase, which phosphorylates cdc25A and targets it for proteasome degradation (Mailand et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these data suggest that the induction of cell division by cytokinins involves increased expression of cycD3. However, the activity of phosphatase cdc25, which activates cyclindependent kinase (CDK) by the removal of a phosphate group from a Tyr moiety in the ATP-binding loop, has also been shown to be cytokinin dependent (Zhang et al, 1996). Redig et al (1996) demonstrated that the zeatin level fluctuates in synchronized tobacco BY-2 cells, peaking at late S and before G2/M transition.…”
mentioning
confidence: 99%
“…Functional homologs of weel+ have been identified in vertebrates, but they have yet to be found in plants. Evidence has been presented for mitotic control by reversible tyrosine phosphorylation of CDKs in cultured plant cells (Zhang et al, 1996).…”
Section: Cell Size Homeostasis In Plantsmentioning
confidence: 99%